2019
DOI: 10.1177/2167702618809367
|View full text |Cite
|
Sign up to set email alerts
|

A Nudge in a New Direction: Integrating Behavioral Economic Strategies Into Suicide Prevention Work

Abstract: Three commonly used behavioral economic strategies were tested to investigate their utility in suicide prevention and mental health initiatives. Study 1 used a social norms nudge to potentially increase the people who accessed an online suicide risk factor intervention via e-mail ( N = 14,792). E-mails containing the social norm nudge were 164% more likely to click on the link relative to those who received the e-mail without the nudge. Study 2 used item count technique to better estimate suicidal ideation com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…Although applicable, the literature applying this framework to STBs is sparse and still emerging. At this time, further study is necessary to understand the factors contributing to suicidal choices (Dombrovski & Hallquist, 2017) as well as the factors that enhance or inhibit the use of prevention strategies (Bauer, Tucker, & Capron, 2019). Toward this end, we offer several suggestions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although applicable, the literature applying this framework to STBs is sparse and still emerging. At this time, further study is necessary to understand the factors contributing to suicidal choices (Dombrovski & Hallquist, 2017) as well as the factors that enhance or inhibit the use of prevention strategies (Bauer, Tucker, & Capron, 2019). Toward this end, we offer several suggestions.…”
Section: Discussionmentioning
confidence: 99%
“…A broad review of discounting in suicidology demonstrates that this line of inquiry has been specific to understanding an individual's propensity for discounting and how this propensity relates to STBs Dombrovski and Hallquist (2017). Although this line of research provides valuable information regarding vulnerability for STBs, many decisions proximally and distally related to suicide (Bauer et al, 2019) have yet to be investigated within this framework. For example, scholars have clear interest in decision‐making processes regarding firearm ownership and storage (Houtsma, Butterworth, & Anestis, 2018), the use (or non‐use) of crisis services (Jaroszewski, Morris, & Nock, 2019), and provider judgment of patient risk (Regehr, LeBlanc, Bogo, Paterson, & Birze, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Using well-known nudges such as social norms and framing techniques could be helpful in overcoming several of these challenges in suicide prevention work. One study by Bauer et al (2019) found that presenting social norms nudges in a sample of college undergraduates increased engagement with an online treatment intervention by 164%. Likewise, a second study consisting of recent ideators ( n = 148) found that ideators who received a social norms nudge (“In a recent study, 97% of people stated that people having suicidal thoughts should seek support”) were more likely to enter a local crisis line phone number into their phone than ideators who did not receive a nudge (Bauer, 2019; Bauer & Capron, 2019b).…”
Section: Nudges In Suicide Prevention Researchmentioning
confidence: 99%
“…Dissemination of skills is another important factor that could help people navigate a time of suicidal crisis, whether it be for themselves or in a peer-support role. One previous study using a framing technique in a general online sample found that people who were asked to learn suicide prevention skills for others who may go through a suicidal crisis in the future were 167% more likely to learn coping skills compared with those who were asked to learn those same skills for themselves (Bauer et al, 2019). A replication study with an online sample of ideators ( n = 118) found that people completed a safety plan more often when it was framed as a way to help other people rather than to help themselves (Bauer, 2019; Bauer & Capron, 2019b).…”
Section: Nudges In Suicide Prevention Researchmentioning
confidence: 99%
See 1 more Smart Citation